Método recepcional e a experiência literária no ensino fundamental: uma aplicação da estética da recepção - Silva, Gabriela Maria de Faria Gonçalves da [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Aesthetics of Reception was created by Jauss and Iser to reformulate literary history, to break with a traditional theory of reading. The literary experience from the theory, materialized by the receptive method, the valorization of the reader and the given voice. The teaching of literature, in perspective, develops translation and transformation skills, progressively, student in editor of literary and non-literary texts. The goal of this work is to transform / broaden the horizons of students' expectations in relation to the themes of the mystery stories and to lead them to assume the role of reader in order to produce comprehensive and critical readings. The question that serves as the north to search for: The Receptive Method, even short number of intervention period, helps the student agent of his process of reading and learning continuously? For its accomplishment, a bibliographical research was made for the necessary appropriation of the theoretical reference of the Reception Aesthetics, and methodological, Receptive Method (Bordini and Aguiar), elaborated to concretize the theory. In addition, the empirical research was carried out, with an interventionist approach, with a qualitative approach, in order to broaden the horizons of students' expectations in relation to the themes of the mystery genre, as proposed by this method. The data were collected by three instruments: audio recording; Daily records of field observations and materials produced by children. Through the analysis of these data, the intervention of the Receptive Method proved productive, considering that the students were expanding their horizons of expectations, that is, there was a progressive learning in relation to the reading of literary and non-literary texts of the genre tale Of mystery. This result points to the certainty that changes in the teaching of reading can and should be done, especially ceasing with the...

Estética da Recepção foi criada por Jauss e Iser para reformular a história literária, romper com a teoria tradicional da leitura. A experiência literária a partir dessa teoria, concretizada pelo Método Recepcional, valoriza o leitor e lhe dá voz. O ensino da Literatura, nesta perspectiva, desenvolve habilidades críticas e transforma, progressivamente, o aluno em leitor de textos literários e não-literários. Assim, neste trabalho, constituiu-se como objetivo geral transformar/ampliar os horizontes de expectativas dos alunos em relação às temáticas dos contos de mistério e levá-los a assumir o papel ativo de leitor, para produzir leituras compreensivas e críticas. A pergunta que serviu de norte para a pesquisa foi: O Método Recepcional, mesmo num curto período de intervenção, contribui para que o aluno seja agente de seu processo de leitura e aprendizagem continuamente? Para sua realização, foi feita uma pesquisa bibliográfica para a necessária apropriação do referencial teórico da Estética da Recepção, e metodológico, Método Recepcional (Bordini e Aguiar), elaborado para concretizar a teoria. Além desta, foi feita a pesquisa empírica, de caráter intervencionista, com abordagem qualitativa, no intuito de ampliar os horizontes de expectativas dos alunos em relação às temáticas do gênero conto de mistério, conforme propõe esse método. Os dados foram coletados por três instrumentos: gravação em áudio; registros diários da observação de campo e materiais produzidos pelas crianças. Por meio da análise desses dados, a intervenção do Método Recepcional mostrou-se produtiva, tendo em vista que os alunos foram ampliando seus horizontes de expectativas, isto é, houve uma aprendizagem progressiva em relação à leitura de textos literários e não literários do gênero conto de mistério. Esse resultado aponta para a certeza de que mudanças no ensino...
Keywords: Ensino fundamental; Leitura; Aprendizagem